The Rights of Victims of Environmental Crimes in Indonesia: Challenges for Legal Reform - Tarigan, Fransisco; Hartiwiningsih, Hartiwiningsih; Rustamaji, Muhammad; Annisa , Intan Baretta Nur; Gunawan, Matthew Marcellinno (Journal of Law, Environmental and Justice, 2025)
Environmental crimes in Indonesia pose significant risks to both the ecosystem and human welfare. Notwithstanding established legal frameworks, the rights of victims of these offences frequently remain insufficiently addressed. This essay analyzes the current state of victim rights regarding environmental crimes in Indonesia, emphasizing the challenges in their enforcement and suggesting pathways for legal reform. Utilising a green victimology framework, it examines the legislative stipulations for victim compensation, restitution, and rehabilitation, juxtaposing them with international benchmarks. This study employs a normative juridical methodology, complemented by case study analysis and an examination of current regulatory instruments, to identify various structural deficiencies, including normative gaps, ineffective law enforcement mechanisms, and the absence of formal procedures for compensation and substantial victim involvement in legal proceedings. The research identifies key obstacles, including insufficient law enforcement, challenges in establishing causation and quantifying damages, restricted access to justice for marginalized groups, corporate influence, and inadequate support systems for victims. The essay ultimately presents policy proposals aimed at strengthening the legislative framework, enhancing enforcement capabilities, advocating for restorative justice, increasing access to justice, and fostering community empowerment to achieve more sustainable environmental justice in Indonesia.